Improving battery safety by utilizing composite phase change material to delay the occurrence of thermal runaway event - Talele, Virendra; Moralı, Uğur; Najafi Khaboshan, Hasan; Patil, Mahesh Suresh; Panchal, Satyam; Fraser, Roydon Andrew; Fowler, Michael W. (Elsevier Ltd, 2024)
Thermal management is a crucial parameter in lithium-ion batteries to maintain the temperature of the batteries within safer working limits. If the optimum working temperature is not maintained, it triggers thermal runaway conditions and causes them to propagate heat from one cell to another within pack level configurations. In battery thermal packaging, several government norms such as GB 38031/32 has suggested that for optimum thermal packaging, there should be a significant delay in the thermal runaway trigger point which can prevent a vehicle from going into catastrophic failure since the driver gets a preventive alert for the high-rise temperature of a cell at an early stage. Delaying thermal runaway occurrence can be effectively achieved by using an integrated layer of PCM. However, present conventional PCMs have a lower thermal conductivity which poses instability in delaying thermal runaway trigger point. This can be improved by using graphene-enhanced composite phase change material, in which the percentage of added extended graphene (EG) determines the improvement in thermophysical property, concisely thermal conductivity of CPCM. The current study examines thermal runaway in widely used cathode materials, LiNiMnCoO2 (NMC) and LiFePO4 (LFP), within a typical large format prismatic cell profile with a commonly used heater-assisted test. The thermal runaway trigger point is monitored for the cases of cell without CPCM and with CPCM to find potential improvement in the delay point. Thermal runaway modeling and statistical safety regime response show that submerging batteries in a CPCM can delay thermal runaway onset by 20 min. When scaling up to a 7S1P battery module level, it is concluded that the smallest addition of EG in CPCM can delay the thermal runaway trigger point and reduce peak temperatures in the battery module over 66 to 113.2 min, which strategically complies with battery safety norms.